The defeat of memory in post-conflict society - Vásquez Cohello, Mario (2017)
Our article contains four times that interweave in order to account for the outcome that has gone through the concept of memory and its relation to transitional justice. We therefore consider it imperative to analyze the current social reality from a special context and how such graphical situation like the domestic violence has been forgotten by its main protagonists: the citizens. This will allow us to understand our present regarding our indifference and ignorance is concerned.It also reviewed the role of history, not as a mere recorder of time, but as the architect of a construction that aims to establish ties with transitional justice so that social coexistence, not to the detriment of the state and a democracy which itself prove to be fragile in structure.